Educação popular em perspectiva eco-relacional: dialogações com a Escola Comunitária Mandacaru, no Centro de Fortaleza-CE - Probo, Paulo Sérgio da Silva (2024)
This work arises from the search for a proposal for critical and liberating education, based on an eco-relational perspective. It is an experience of building partnership and affectionate paths with the educators of the Mandacaru Community School in their educational work. Located in the center of Fortaleza, Ceará, Mandacaru focuses on the education of young people and adults living on the streets, overcoming street situations, vulnerability and social exclusion. The aim of this study was to analyze the experiences of these educators, which emerged as a group from their experiences with the contributions of popular education and the eco relational perspective. To this end, we opted for Engaged Research, with a qualitative approach, where, through the formation of a learning group, we were able to experience and construct these contributions in a dialogical way. Observing the meetings showed that the educators were willing to work together to build a plan for the school based on these approaches.